A Case of Primary Diffuse Leptomeningeal Gliomatosis Predominantly Involving the Cervical Spinal Cord and Mimicking Chronic Meningitis - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2010)
Gliomas may rarely arise in the leptomeninges without any evidence of intraaxial involvement. A case of primary diffuse leptomeningeal gliomatosis (PDLG) histologically diagnosed as oligoastrocytoma is presented. A 50-year-old woman presented with nausea, vomiting and headache. Magnetic resonance imaging (MRI) of cranium and cervical region revealed dural thickening starting from the craniocervical junction to the level of C4 without any parenchymal lesions. CSF examination showed an increase in protein and decrease in glucose levels. There were neither any kind of atypical cells nor any kind of growth in bacterial cultures. The patient underwent biopsy at the level of Cl for diagnosis. The specimen was diagnosed as primary diffuse leptomeningeal gliomatosis, with phenotypic features of astrocytoma and oligodendroglioma.
Keywords: Glial tumor; Meningitis; Primary diffuse leptomeningeal gliomatosis; CEREBROSPINAL GLIOMATOSIS; OLIGODENDROGLIOMA; MR